ANALISA PEMBENTUKAN KARAKTER ANAK MELALUI PEMBELAJARAN SENI GERAK TARI PADA MASA PANDEMI - Zannatunnisya Zannatunnisya (Jurnal Abdi Ilmu, 2020)
Early childhood education is important for a indonesian generation. It is the potential period in the growth of children to gain exploration experience from all aspects of both motoric and psychomotor. Lack of knowledge, especially about the concept and purpose of performing arts from an early age for education influence the design of learning programs that tend to be less creative. Even though in motion, there are many ways where the teacher can creatively connect with the values of student life at large the need for well-designed performing arts should be provided. This study aimed to describe how to produce performing arts learning design in kindergarten school by utilizing local cultural excellence knowledge sources (local genius knowledge) of Medan with the concept of integrated learning. This study used qualitative phenomenological research. The results show that during pandemic students can still learn the art performing by using online media (WhatsApp video call) so students can be more creative and discover the latest movements with the assistance of parents at home.